PERHITUNGAN RAB STRUKTUR GEDUNG DAN PENJADWALAN PROYEK SMP RAJAWALI BANGSA KOTA AMBON - Sukma Toisuta; La Mohamat Saleh; Delvia Rimesye Apalem (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Cost and time calculations are indispensable in project implementation, namely cost budget management to help carry out the work. For real conditions in the field, the data obtained is only limited to working drawings while the data on the calculation of the Budget Plan Cost (RAB) and Time Schedule of the project is not obtained.The purpose of this study is to calculate the Budget Plan Cost (RAB) of the Rajawali Bangsa Junior High School building structure using AHSP in 2023 and plan the time schedule for the Rajawali Bangsa Junior High School building structure using the S Curve method. In this study the authors calculated the RAB using AHSP in 2023 and project scheduling using the S Curve method.The results of the calculations that have been carried out in this study obtained the cost required for the structure of the SMP Rajawali Bangsa building in Ambon City amounting to Rp 2.601.513.000,00 and the project scheduling calculated and planned using the S curve method on the structure of the SMP Rajawali Bangsa building in Ambon City resulted in a project implementation time schedule of 127 calendar days. Keywords: Building Structure, Project Scheduling, RAB